Characterizations of fuzzy M-Γ-hemirings - Jianming Zhan; Deng Pan (Journal of Hyperstructures, 2013)
In this paper, the concepts of M-fuzzy left h-ideals (right h-ideals, h-bi-ideals, h-quasi-ideals) in M-Γ-hemirings are introduced. Some new properties of these kinds of M-fuzzy hideals are also given. Finally, we show that h-hemiregular, hintra-hemiregular and h-quasi-hemiregular M-Γ-hemirings can be described by M-fuzzy left(right) h-ideals, M-fuzzy h-bi-ideals and M-fuzzy h-quasi-ideals, respectively.